Pendekatan Dakwah Jama'ah Tabligh dalam Meningkatkan Ketaatan Beragama Masyarakat - Yudi Andrian (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2019)
Abstract Jama'ah Tabligh is one of the da'wah movements that has sincerity to invite the community to obey Allah by practicing religion perfectly in accordance with the example of the king of the Prophet, especially inviting to practice the five daily prayers in congregation. Approach Jama'ah Tabligh by performing (silaturahim) from house to house which in this case uses a psychological approach to invite (persuasive), invites to obey God. Educational approach by holding religious lectures (bayan) on the importance of faith in good deeds in the mosque, the efforts of Jama'ah Tabligh by using this method have not been fully influential because there is another approach which is forgotten by Jama'ah Tabligh, which is a cultural approach. The Tabligh Jama'ah approach in increasing religious adherence to the community by visiting Muslim brothers from house to house (jaulah), conveyed the importance of faith and good deeds in the information majlis (Bayan), and ta'lim has not been influential especially in the effort to invite the public to obey Allah SWT, follow the way of the Prophet Muhammad. Because Jama'ah Tabligh in the approach taken has not been able to adjust to the culture of the community in accordance with the conditions of the community and Jama'ah Tabligh in his da'wah approach forgets an approach, namely the Cultural approach.